Police training and police violence in Scandinavia - Eliasson, Michelle N. (Police conflict management ; volume 2: Training and education, 2023)
Compared to countries such as the United States, in Scandinavian countries there tend to be fewer violent confrontations between police officers and civilians. In many countries where there are low rates of police violence the public has high trust in the police and high rates of feeling safe compared to countries with a high level of police violence. In order to understand how to improve the public’s trust in the police and improve community relationships with the police, scholars have explored notions such as training, organizational structure, police practices, and strategies. Furthermore, police agencies and policing models in other regions, such as Scandinavia, are often studied due to the lower levels of violent encounters between citizens and the police and the extensive training officers receive. Police training is one of the factors most often discussed when examining ways of reforming the police and changing officers’ conduct in various situations such as violent encounters, misconduct, and efficiency. Thus, Scandinavian police agencies are often of particular interest to scholars doing comparative work in the area of policing. This chapter will review the current literature on police agencies in Scandinavia, their use of force, and the Scandinavian peoples’ perception of the police. It will also make recommendations for future research on police training and the role it plays in police conduct, drawing on the knowledge from Scandinavian policing.